(untitled) (Eurasian Journal of Philology Science and Education, 2015)
Literary process in Great Britain is determined not only by binding of realism, nonrealism and postmodern literature. A lot of adjoining phenomena appeared on the stage must be taken into account by literary men of modern times. Symbiosis of these directions is real fact that has already been approved.